Acute coronary syndrome demonstrating plaque rupture in calcified plaque visualized by optical coherence tomography and near-infrared spectroscopy combined with intravascular ultrasound. Issue 4 (October 2021) - Sasahira, Yoshitaka; Kume, Teruyoshi; Koto, Satoshi; Hiroshi, Okamoto; Yamada, Ryotaro; Neishi, Yoji; Uemura, Shiro
Abstract: Optical coherence tomography (OCT) can visualize calcification of the coronary plaque as a low-intensity lesion with sharp borders. However, residual lipid tissue inside the calcification could pose a problem in plaque evaluation by OCT. We present a case of acute coronary syndrome (ACS) demonstrating plaque rupture in the calcified plaque. In this case, OCT demonstrated a cavity suspected to represent rupture in the calcified plaque and near-infrared spectroscopy revealed a lipid component behind the calcified plaque. Although calcified plaque is not considered a reason for ACS except for calcified nodules, residual lipid tissue inside the calcification might cause ACS if the thin fibrous cap over the lipid tissue is disrupted, even if surrounded by calcification. <Learning objective: This is the first case report to describe plaque rupture in calcified plaque visualized by OCT and near-infrared spectroscopy. Lipid tissue surrounded by calcification is generally recognized as calcified plaque on OCT because discrimination between lipid tissue and calcification is based on border characteristics. Residual lipid tissue within calcification could pose a problem in plaque evaluation by OCT.>